Preparation, characterization and catalytic activity of gold nanoparticles stabilized by poly (n-vinylpyrrolidone) and poly (N,N-dimethyl-N,N-diallylammonium chloride) - Baigaziyeva, E.K.; Schuette, K.; Tatykhanova, G.S.; Janiak, C.; Kudaibergenov, S.E. (Recent Contributions to Physics, 2012)
Optical properties, structure and morphology of colloidal gold nanoparticles (AuNPs) stabilized by poly (N-vinylpyrrolidone) (PVP) and poly(N,N-dimethyl-N,N-diallylammonium chloride) (PDMDAAC) were characterized by visible spectroscopy, X-ray diffraction (XRD) and scanning electron microscopy (SEM). The influence of the molecular weight (Mw) of PVP on the size of AuNPs was studied. The catalytic activity of polymer-protected AuNPs with respect to hydrogenation of p-nitrophenol was studied. High conversion degree of 4-nitrophenol to 4-aminophenol was found.
Keywords: colloidal gold nanoparticles, optical properties, structure, morphology